High-density mapping in catheter ablation for persistent atrial fibrillation. (19th May 2022) - Steven, D; Fiedler, L; Roca, I; Lorgat, F; Lacotte, J; Haqqani, H; Jesser, E; Williams, C; Roithinger, F
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Abbott Laboratories Background: Pulmonary vein isolation (PVI) is an established treatment option for persistent atrial fibrillation (PersAF). Corresponding long-term success rates remain modest however, advancements in high-density (HD) mapping may better identify substrates. The HD grid-style mapping catheter (HD Grid) allows for simultaneous analysis of adjacent orthogonal bipolar signals that may assist in ablation strategy decisions to achieve favorable outcomes in treating PersAF. Objective: This was a prospective, multi-center, observational study to quantify and characterize the use of a market-released HD mapping catheter in PersAF subjects. Methods: HD Grid was used in PersAF subjects undergoing radiofrequency (RF) ablation across 25 sites to gather data regarding safety, mapping efficiency and quality, ablation strategies, and procedural outcomes. Results: 334 PersAF subjects (average age: 64.2 years; 76% male) were enrolled in this study. Types of maps generated included peak-to-peak voltage (78%; 322/413), local activation time (LAT) (11.4%; 47/413), and complex fractionated electrogram (CFE) mean (7.7%; 32/413). Median total mapping points collected and used were 8428.0 (IQR 4845.0-13366.0) and 2099.0 (IQR 1219.0-2947.0), respectively, in a median of 11.0 (IQR 7.3-16.0) minutes per map. Low voltage, scar/fibrosis, and CFE were searched for in 90.4% (302/334), 53.6% (179/334), and 15.9% (53/334) of subjects, respectively. A PVI approach was used in 93.1% of all ablation procedures and 34.1% (114/334) of subjects received PVI plus additional lesions. HD Grid identified signals of interest not identified by the ablation catheter in 80.4% (205/255) of subjects. The total procedure time was 134.3 ± 51.3 minutes with a fluoroscopy time of 14.5 ± 11.3 minutes and RF ablation time of 32.4 ± 29.6 minutes. Of the subjects in atrial fibrillation (AF) (59.6%; 199/334), AF was terminated in 80.4% (160/199). 87.4% (173/198) of subjects were free from recurrent atrial arrhythmias as detected by 48-hour Holter monitoring at 12 months. 13.8% (46/334) of subjects experienced any adverse event through 12 months including 1 death unrelated to the procedure and 1 event deemed related to HD Grid by the investigator. Conclusion: This study demonstrated the use of the HD Grid mapping catheter to create detailed maps and to guide ablation strategies to treat PersAF while maintaining an adequate safety profile.